Computerised personal identification number code controlled locking system / Mohd Asri Muhammad Ali - Muhammad Ali, Mohd Asri (1995)
This paper described the development of computer based controlled lock system that control the opening and closing of door or entrance of restricted rooms and building for security reasons. It will permit entry to only authorised personals keying correct personal identification numbers through an input port. The system is driven by a software which compute and compare the input data with that of the system data. Relevant command signals will be generated to activate the driver relays to energise locking mechanism. Software developed allows the operation of the system to be more flexible. To open the door, to allow access for only certain pre set duration before it automatically de energised to close the door again.